Investigation of the Performance of Two Passive Controllers in Mitigating the Rotational Response of Irregular Buildings - Yasser Bigdeli; Dookie Kim (Advances in Materials Science and Engineering)
Two passive vibration control devices (i.e., circle type tuned liquid damper (C-TLD) and a circle type tuned liquid column damper (C-TLCD)) were experimentally investigated for their performance when attached to the irregular building structure subjected to dynamic loads. The specific directions where the maximum response of the structure is expected were experimentally identified for x- and y-directions as well as for rotational direction. The power spectral density (PSD) was computed for the response of the structure based on the frequency of the first three modes and also water level changes in the device container by using fast Fourier transform (FFT). The performances of these two controllers regarding suppressing the structural vibration were compared for the seismic loads applied in an experimentally identified critical direction. The results show that these systems are effective in terms of mitigating the coupled lateral and torsional vibrations of a scaled three-story irregular model.